Optimization of emission cost and economic analysis for microgrid by considering a metaheuristic algorithm-assisted dispatch model - Somakumar R.; Kasinathan P.; Monicka G.; Rajagopalan A.; Ramachandaramurthy V.K.; Subramaniam U. (John Wiley and Sons Ltd, 2023)
Cost benefit analysis; Cost functions; Costs; Diesel engines; Economic analysis; Electric load dispatching; Electric power system economics; Electric power transmission networks; Genetic algorithms; Iterative methods; Natural resources; Renewable energy resources; Solar power generation; Cost analysis; Dispatch model; Economics analysis; Emission costs; High demand; Meta-heuristics algorithms; Microgrid; Optimisations; Power grids; Renewable energy source; Fuel cells